The multidimensional effects of extensive listening on EFL learners - Chang, Anna C-S; Renandya, Willy Ardian (Universitas Islam Malang, 2024)
This study investigated the multidimensional effects of extensive listening (EL) on learners’ actual language gains, selection of study materials, and practice styles. Language gains were measured through a pre- and a post-test on students’ aural vocabulary test (Listening Vocabulary Levels Test, LVLT) and general listening comprehension (TOEIC), administered before and after the intervention. Fifty-five university student participants took part in the four-month experiment; they were entirely free to select their favorite study materials online or off-line. The results showed that each student spent an average of 1,387 minutes (approximately 87 minutes per week) doing EL practice. The three most popular study materials were the following: Songs (63.64%), movies (49.09%), and talks (43.46%); materials were mainly from YouTube (74.55%), Netflix (49.09%), and other miscellaneous sources (43.63%). Their practice style was unanimously a combination of viewing and listening. From the pre-tests to the post-tests, students made significant gains in both LVLT and TOEIC, but the effect sizes were small. Some suggestions are made for implementing EL.